2020
DOI: 10.3390/ijerph17072349
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Urban Park Access Using House-Level Data in Urban China: Through the Lens of Social Equity

Abstract: The various benefits of urban green space are gaining increasing attention nowadays. Hence, the distribution of green space has become a scrutinized concern for spatial equity among local governments and the planning scholars. This study is the first quantitative evaluation of urban park accessibility using house-level data in urban China, from the perspective of social equity. We chose Nanjing as the empirical case and examined 2709 real estate units and 79 parks within the city. Accessibility is measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 49 publications
(154 reference statements)
1
35
1
Order By: Relevance
“…This work has not considered the quality of the parks as a factor of environmental justice because urban green areas are relevant for the urban quality of life and for promoting environmental equity [46]. For their part, some authors [47] believe that in order to determine environmental justice, the accessibility and availability of green areas, you have to also consider their quality. The results from their analysis, combined with the socioeconomic characteristics, broaden the understanding of environmental justice with respect to the parks.…”
Section: Discussionmentioning
confidence: 99%
“…This work has not considered the quality of the parks as a factor of environmental justice because urban green areas are relevant for the urban quality of life and for promoting environmental equity [46]. For their part, some authors [47] believe that in order to determine environmental justice, the accessibility and availability of green areas, you have to also consider their quality. The results from their analysis, combined with the socioeconomic characteristics, broaden the understanding of environmental justice with respect to the parks.…”
Section: Discussionmentioning
confidence: 99%
“…While urban green canopies derived from remotesensing methods such as satellite images could quantify urban green spaces [49], they fail to evaluate people's sensory functions. In addition, this kind of intuitive perception of residents, GVI, also takes the human-oriented perspective into consideration, giving a novel comprehension compared to former studies based on the accessibility of different social groups to urban parks [23,28,50]. An indicator based on residents' demand-side perceptions is used to replace the supply side accessibility calculated for urban green spaces.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…In addition, Nesbitt et al concluded that social groups with highereducation degrees and higher incomes have more access to urban vegetation in 10 US cities [22]. Another study in Nanjing, China, revealed that the accessibility of urban parks is positively related to housing prices and negatively related to the age of buildings [23]. According to the former studies, urban parks, urban green spaces, and street greenery, which might be accessible more frequently in daily life, should be focused on to evaluate the equity of its spatial distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The distance calculation method has also experienced the transformation from Euclid distance and Manhattan distance to network distance based on the urban road network. With the development of network analysis module of GIS, more and more vector-based road network distance assessment methods have been applied to the study of spatial equity [9,14,15] 。…”
Section: Computational Models Of Spatial Equitymentioning
confidence: 99%